2013
DOI: 10.1177/1721727x1301100202
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Importance of Simple Phenolic Compounds on Inflammation, Cell Proliferation and Apoptosis with a Special Reference to β-D-Salicin and Hydroxybenzoic Acid

Abstract: Simple phenolic (SP) compounds are natural products that exhibit multiple pharmacological functions. The best known of these compounds is β-D-salicin, the first discovered phenolic glycoside and salicylic acid, or 2-hydroxybenzoic acid (2-HBA). Both of these compounds have attracted the interest of scientists in various interdisciplinary fields, including chemistry, pharmacology and medicine. Although β-D-salicin is found in various plants, it is often associated with willow, as it was first discovered in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…In this respect, the reactivity of these molecules derives from their functional groups (mainly carboxylic), which is influenced by substituted hydroxyl groups at 2-, 3-, and 4-positions. Our previous research indicated that 4-HBZn selectively inhibited COX-2 and its transcription compared to ASA [6]. These complexes exhibited different cytotoxic and apoptotic effects in HT-1080 cells, suggesting different environments of interaction, and hence exhibit different efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, the reactivity of these molecules derives from their functional groups (mainly carboxylic), which is influenced by substituted hydroxyl groups at 2-, 3-, and 4-positions. Our previous research indicated that 4-HBZn selectively inhibited COX-2 and its transcription compared to ASA [6]. These complexes exhibited different cytotoxic and apoptotic effects in HT-1080 cells, suggesting different environments of interaction, and hence exhibit different efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, monovalent (Na + ) and divalent (Ca 2+ ) 2-HB complexes were also found to exhibit these biological effects but at concentrations between 2 and 20 mM [6,13,14]. Generally, each organometallic complex has its own chemical/biochemical mode of interaction, particularly in terms of interactions with DNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…clinopodioides [44,80] Inhibition of mucin production and secretion in airways epithelial cells [83] Hepatoprotective [84] Potential inhibitor of CDK4 in retinoblastoma [85] Neuroprotective [86] Inhibition of acetylcholinesterase [87] Anti-inflammatory [88]; Anti-inflammatory in vivo [89] Depressant effect on CNS [ [80] Effect on cardiovascular system reviewed [117] Pharmacological importance reviewed [118] O H…”
Section: Linarin (8)mentioning
confidence: 99%
“…Rosmarinic acid (19) Z. clinopodioides [80] Review on pharmaceutical and clinical usage [113] Neuroprotective-review [114] General review on applications [115] Review on anticancer potential [116] O [80] Effect on cardiovascular system reviewed [117] Pharmacological importance reviewed [118] O H…”
Section: O H O Och 2 Chmentioning
confidence: 99%